(untitled) (Research, Society and Development, 2019)
This article examines the nature of philosophy and discusses the use of an appropriate methodology for the teaching of Philosophy at the High School level. The objective was to investigate the specific nature of Philosophy teaching and its articulation with the development of critical reflection, creative and instituting new realities, having as a reference the sensitization, problematization, investigation and conceptualization. A bibliographical research was carried out, starting from the theoretical-methodological proposal of Gallo, for the teaching of philosophy. The existence of discipline in the curriculum of schools and the necessity of the exercise of philosophy is not enough, but it is necessary to think about the method that enables the formation of subjectivity and the production of new concepts and contents and that mobilizes the construction of new knowledge and actions. It was concluded that a methodological inspiration for the teaching of philosophy should take into account the reality of each institution, as well as the ability of each teacher to redo and adapt the proposal through a constant work of constructing Philosophy itself, which stimulates ethical-critical thinking.